Adropin reduces blood glucose levels in mice by limiting hepatic glucose production. Issue 8 (19th April 2019) - Thapa, Dharendra; Xie, Bingxian; Manning, Janet R.; Zhang, Manling; Stoner, Michael W.; Huckestein, Brydie R.; Edmunds, Lia R.; Zhang, Xueyang; Dedousis, Nikolaos L.; O'Doherty, Robert M.; Jurczak, Michael J.; Scott, Iain
Abstract: Adropin is a liver‐ and brain‐secreted peptide hormone with striking effects on fuel metabolism regulation in a number of tissues. Previous studies demonstrated that adropin secretion is decreased in obese mice subjected to a long‐term high‐fat diet (HFD), and that whole‐body loss of adropin expression resulted in systemic insulin resistance. Treatment of obese mice with adropin improves glucose tolerance, which has been linked to increased glucose oxidation and inhibition of fatty acid utilization in isolated skeletal muscle homogenates. In this study, we used in vivo physiological measurements to determine how treatment of obese mice with adropin affects whole‐body glucose metabolism. Treatment with adropin reduced fasting blood glucose and, as shown previously, increased glucose tolerance in HFD mice during standard glucose tolerance tests. Under hyperinsulinemic‐euglycemic clamp conditions, adropin treatment led to a nonsignificant increase in whole‐body insulin sensitivity, and a significant reduction in whole‐body glucose uptake. Finally, we show that adropin treatment suppressed hepatic glucose production and improved hepatic insulin sensitivity. This correlated with reduced expression of fatty acid import proteins and gluconeogenic regulatory enzymes in the liver, suggesting that adropin treatment may impact the pathways that drive vital aspects of hepatic glucose metabolism. Abstract : Adropin is a liver‐ and brain‐secreted peptide hormone with striking effects on fuel metabolism regulation in a number of tissues. In this study, we used in vivo physiological measurements to determine how treatment of obese mice with adropin affects whole‐body glucose metabolism. We show that adropin treatment suppressed hepatic glucose production, which correlated with reduced expression of fatty acid import proteins in the liver, suggesting that adropin treatment may impact the bioenergetic pathways needed to drive hepatic metabolism.